Diamond Springs, Morris County - Blythe, Meghan A. (Kansas State University, The Chapman Center for Rural Studies, 2012)
Diamond Springs first began as a supply point on the Santa Fe Trail, but proslavery forces destroyed it in 1863. After the Civil War, settlers from Illinois founded a new Diamond Springs about three miles south of the original site.
Meghan A. Blythe, “Diamond Springs, Morris County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/137.
Keywords: Civil War; Council Grove; Diamond Springs; Morris County; Samuel Kingman; Santa Fe Trail